52 Effect of external application of spikenard water decoction on the mouse pain model. (19th December 2016) - Xi, Peng; Li, Yan; Ge, Xiaojin; Miao, Mingsan
Abstract : Objectives: To investigate the effects of external application of a spikenard water decoction on pain model mice. Methods: We investigated the effects of spikenard water decoction on the pain threshold in mice using the hot plate method. After injection of formaldehyde, the effects of spikenard water decoction on the formalin-induced pain incubation period and biting times were observed. Results: Each dose of spikenard water decoction obviously or significantly improved the pain threshold of pain model mice ( p ?<?0.01, p < 0.05), significantly prolonged the pain licking incubation period ( p <0.01) and obviously or significantly reduced the number of instep licks in 5 min and 10 min ( p < 0.01, p < 0.05). Conclusions: External application of spikenard water decoction has a good analgesic effect in the mouse pain model.